STANDARD MANUFACTURING PROCESS OF DVIGUNA BALIJARITA RASASINDURA - Kumar Singh, Sanjay; Singh Rathor, Amar; Prajapati, P K (International Journal of Ayurveda and Pharma Research, 2015)
Introduction: Preparation of herbo-mineral compounds in Ayurveda revolves around mercury, considered as the prime among all minerals. Sulphur is again an important element used in many disorders and applied substance in different Ayurvedic formulations, considered as the antidote for the harmful mercurials. Kajjali is prepared by grinding mercury and sulphur. The prepared Kajjali used as a raw material for Rasasindura preparation with Kupipakva method. Kupipakva method is developed by ancient Rasaacharya for the preparation of heat treated mercurial. Dviguna gandhak jarita parada is considered more potent compare to Samaguna bali jarita. Objective: To study Kupipakva kalpana with preparation of Dviguna-bali jarita Rasa sindura. Methodology: Whole process is divided and performed as Sodhana of contents (Hingula and gandhaka), Hingulotth parada extraction, Kajjali preparation, preparation of Dviguna balijarita Rasa sindura. Observation: Hingula after Shodhana became soft and lusterless compound and Gandhaka becomes granular and brittle. Hinguloth parada extraction by Kanduka yantra method shown more yield compared to other methods. Kajjali preparation took 96 hours of Mardana of contents with Nischandra property. It took 48 hours for Dviguna Bali Jarita Rasasindura preparation by Kupipakva kalpana method with a yield of 106g. Conclusion: Preparation of Dviguna Balijarita Rasasindura needs more duration of heat treatment in every step of graded heating pattern of Kupipakva kalpana. The heating pattern is proportional to its therapeutic efficacy.